Profitabilitas Jamur Tiram Putih pada Unit Usaha Bionuisi - Halimah, Andi Sitti; Nadja, Rahmawaty A. (Universitas Galuh, 2024)
A horticultural commodity that is starting to gain interest in cultivation is the white oyster mushroom (Pleurotus ostreatus). Even though they are not a new food ingredient for society, the position of oyster mushrooms has now been accepted by the public as a healthy food ingredient. Several studies conducted on mushroom agribusiness show business developments that encourage the expansion of production land, even though this commodity from a promising economic aspect does not require large areas of land. This research aims to analyze the profitability of UKM Bionuisi in Rajang Village, Lembang District, Pinrang Regency. The calculations start from cost and income analysis, break-even analysis (BEP), and profitability. The research results show that the total costs incurred during 2022 are IDR 62,621,429 with total income of IDR 365,750,000 received from three products sold by UKM Bionuisi in a year, namely baglog, chips and fresh white oyster mushrooms. Among the three products, fresh white oyster mushrooms are the UKM product that provides the largest income because they can sell up to 1 ton in 2022 and this has a positive impact on the profitability of UKM Bionuisi by up to 74.94%.